2017
DOI: 10.1007/s11747-017-0568-z
|View full text |Cite
|
Sign up to set email alerts
|

Marketers’ use of alternative front-of-package nutrition symbols: An examination of effects on product evaluations

Abstract: How front-of-package (FOP) nutrition icon systems affect product evaluations for more and less healthful objective nutrition profiles is a critical question facing food marketers, consumers, and the public health community. We propose a conceptually-based hierarchical continuum to guide predictions regarding the effectiveness of several FOP systems currently used in the marketplace. In Studies 1a and 1b, we compare the effects of a broad set of FOP icons on nutrition evaluations linked to health, accuracy of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
77
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 34 publications
4
77
0
1
Order By: Relevance
“…To assess the impact of these labels, we harvested 1594 effects from 114 studies between 1996 and 2018, across different fields (marketing and consumer studies, nutrition science, public health, sensory science, medicine, and others). Drawing from extant literature (Cadario and Chandon 2018;Ducrot et al 2015;Hodgkins et al 2012;Kanter et al 2018;Newman et al 2018), we classify FOP labels into reductive and interpretative and further distinguish between interpretative nutrient-specific labels and summary indicator labels. This typology allows us to identify the key aspects influencing the effectiveness of FOP labeling and the type of information most beneficial for consumers.…”
mentioning
confidence: 99%
“…To assess the impact of these labels, we harvested 1594 effects from 114 studies between 1996 and 2018, across different fields (marketing and consumer studies, nutrition science, public health, sensory science, medicine, and others). Drawing from extant literature (Cadario and Chandon 2018;Ducrot et al 2015;Hodgkins et al 2012;Kanter et al 2018;Newman et al 2018), we classify FOP labels into reductive and interpretative and further distinguish between interpretative nutrient-specific labels and summary indicator labels. This typology allows us to identify the key aspects influencing the effectiveness of FOP labeling and the type of information most beneficial for consumers.…”
mentioning
confidence: 99%
“…According to the classification of FOP nutrition labels (Newman et al 2018;Ikonen et al 2020), all of these are "interpretive" because they repeat some of the descriptive nutrition information present on the back of the package but enhance it with graphical symbols (e.g., colors, bar charts, more or less filled triangles) that help to convey the nutritional quality of each nutrient or of the food product as a whole. This is true even for Nutri-Repère, the least "enhanced" label, where a bar chart allows consumers to see at a glance the contribution of the product to daily nutritional requirements.…”
Section: Methods Stimulimentioning
confidence: 99%
“…FOP nutrition labels provide summary, simplified information about the calorie and/or nutrient content of foods on the front of the pack, sometimes augmented with evaluative symbols or color coding (McGuire 2012;Newman et al 2018). They should not be confused with various other FOP information such as warning labels (e.g., "contains Sulfites"), health or structure/function claims (e.g., "calcium helps create strong bones''), unregulated food claims (e.g., "natural"), or the regulated nutrient claims such as the "low-fat", "no trans-fat" or "extra antioxidants" studied by Kiesel and Villas-Boas (2013) or by Belei et al (2012).…”
Section: Front-of-package Nutrition Labelingmentioning
confidence: 99%
“…Another food label that is important to consumers when purchasing foods is the nutritional content label. Several studies like those of Hwang et al (2016); and Newman et al (2017) found that in order to eat healthier more consumers are making purchasing decisions based on nutrition labels. Many countries have even passed laws enforcing package nutrition labels.…”
Section: Literature Reviewmentioning
confidence: 99%